Expression of steroid 5α‐reductase isozymes in prostate of adult rats after environmental stress. (22nd November 2012) - Sánchez, Pilar; Torres, Jesús M.; Castro, Beatriz; Olmo, Asunción; del Moral, Raimundo G.; Ortega, Esperanza
<x xml:space="preserve">Abstract</x> The elevated incidence of prostate cancer and benign prostatic hypertrophy is a cause of increasing public health concern in the Western world. The normal and pathological growth of the prostate are both dependent on stimulation by dihydrotestosterone, which is synthesized from circulating testosterone by two 5α‐reductase (5α‐R) isozymes, 5α‐reductase type 1 (5α‐R1) and 5α‐reductase type 2 (5α‐R2). Both isozymes have been implicated in prostate disease. We used quantitative RT‐PCR and immunohistochemistry, respectively, to quantify mRNA and protein levels of 5α‐R isozymes in the ventral prostate of adult rats under environmental stress conditions analogous to those found in some common workplace situations, i.e. artificial light, excessive heat, and the sensation of immobility in a small space. Transcription and expression levels of both 5α‐R isozymes were significantly higher in environmentally stressed rats than in unstressed rats. Increased 5α‐R isozyme levels may play a role in the development or maintenance of prostate disease. Further research is warranted to explore these effects of environmental stress on human health and their implications for environmental and occupational health policies.